TOURISM GOVERNANCE: BUMDES AS THE SPIRIT OF COMMUNITY ECONOMIC EMPOWERMENT - Mayarni Mayarni; Hasim As'ari; Adianto . (Universitas Padjadjaran, 2021)
This study aims to determine the development of the Napangga Lake tourist attraction in Kepenghuluan Tanjung Medan, Rokan Hilir Regency, which greatly contributes to village-owned enterprises in empowering the community’s economy. Lake Napangga is a new destination located in the Rokan Hilir area and has very promising tourism potential, so it must be managed professionally and have an economic impact on the local community. Therefore, village-owned enterprises must be able to become a spirit in developing this lake tourism object in order to empower the economy of the village community. This research uses a qualitative approach with a case study method, where data collection is done by observation and interviews. After the data and information are obtained, it will be analyzed in depth with data triangulation validity test. The results of this study found that the development of the Lake Napangga tourist attraction has not run optimally by the Bumdes in empowering the community’s economy. This is due to the inconsistency in the number of tourists visiting Lake Napangga, because this tour is still seasonal. Strategies are needed to make economic empowerment for the community in order to increase income and improve the quality of life of the surrounding community.